I am trying to understand what is meant by "deterministic" in expressions such as "deterministic context-free grammar". (There are more deterministic "things" in this field). I would appreciate an example more then the most elaborate explanation! If possible.
My primary source of confusion is from not being able to tell how this property of a grammar is different from (non-)ambiguity.
The closest I got to finding what it means is this quote from the paper by D. Knuth On the Translation of Languages from Left to Right:
Ginsburg and Greibach (1965) have defined the notion of a deterministic language; we show in Section V that these are precisely the languages for which there exists an L R ( k ) grammar
which becomes circular as soon you get to the Section V
, because there it says that what LR(k) parser can parse is the deterministic language...
Below is an example that I could find to help me understand what "ambigous" means, please take a look:
onewartwoearewe
Which can be parsed as one war two ear ewe
or o new art woe are we
- if a grammar allows that (say it has all the words I just listed).
What would I need to do to make this example language (non-)deterministic? (I could, for example, remove the word o
from the grammar, to make the grammar not ambiguous).
Is the above language deterministic?
PS. The example is from the book Godel, Esher, Bach: Eternal Golden Braid.
Let's say, we define the grammar for the example language like so:
S -> A 'we' | A 'ewe'
A -> B | BA
B -> 'o' | 'new' | 'art' | 'woe' | 'are' | 'one' | 'war' | 'two' | 'ear'
By the argument about having to parse the whole string, does this grammar make the language non-deterministic?
let explode s =
let rec exp i l =
if i < 0 then l else exp (i - 1) (s.[i] :: l) in
exp (String.length s - 1) [];;
let rec woe_parser s =
match s with
| 'w' :: 'e' :: [] -> true
| 'e' :: 'w' :: 'e' :: [] -> true
| 'o' :: x -> woe_parser x
| 'n' :: 'e' :: 'w' :: x -> woe_parser x
| 'a' :: 'r' :: 't' :: x -> woe_parser x
| 'w' :: 'o' :: 'e' :: x -> woe_parser x
| 'a' :: 'r' :: 'e' :: x -> woe_parser x
(* this line will trigger an error, because it creates
ambiguous grammar *)
| 'o' :: 'n' :: 'e' :: x -> woe_parser x
| 'w' :: 'a' :: 'r' :: x -> woe_parser x
| 't' :: 'w' :: 'o' :: x -> woe_parser x
| 'e' :: 'a' :: 'r' :: x -> woe_parser x
| _ -> false;;
woe_parser (explode "onewartwoearewe");;
- : bool = true
| Label | Pattern |
|---------+--------------|
| rule-01 | S -> A 'we' |
| rule-02 | S -> A 'ewe' |
| rule-03 | A -> B |
| rule-04 | A -> BA |
| rule-05 | B -> 'o' |
| rule-06 | B -> 'new' |
| rule-07 | B -> 'art' |
| rule-08 | B -> 'woe' |
| rule-09 | B -> 'are' |
| rule-10 | B -> 'one' |
| rule-11 | B -> 'war' |
| rule-12 | B -> 'two' |
| rule-13 | B -> 'ear' |
#+TBLFM: @2$1..@>$1='(format "rule-%02d" (1- @#));L
Generating =onewartwoearewe=
First way to generate:
| Input | Rule | Product |
|-------------------+---------+-------------------|
| '' | rule-01 | A'we' |
| A'we' | rule-04 | BA'we' |
| BA'we' | rule-05 | 'o'A'we' |
| 'o'A'we' | rule-04 | 'o'BA'we' |
| 'o'BA'we' | rule-06 | 'onew'A'we' |
| 'onew'A'we' | rule-04 | 'onew'BA'we' |
| 'onew'BA'we' | rule-07 | 'onewart'A'we' |
| 'onewart'A'we' | rule-04 | 'onewart'BA'we' |
| 'onewart'BA'we' | rule-08 | 'onewartwoe'A'we' |
| 'onewartwoe'A'we' | rule-03 | 'onewartwoe'B'we' |
| 'onewartwoe'B'we' | rule-09 | 'onewartwoearewe' |
|-------------------+---------+-------------------|
| | | 'onewartwoearewe' |
Second way to generate:
| Input | Rule | Product |
|-------------------+---------+-------------------|
| '' | rule-02 | A'ewe' |
| A'ewe' | rule-04 | BA'ewe' |
| BA'ewe' | rule-10 | 'one'A'ewe' |
| 'one'A'ewe' | rule-04 | 'one'BA'ewe' |
| 'one'BA'ewe' | rule-11 | 'onewar'A'ewe' |
| 'onewar'A'ewe' | rule-04 | 'onewar'BA'ewe' |
| 'onewar'BA'ewe' | rule-12 | 'onewartwo'A'ewe' |
| 'onewartwo'A'ewe' | rule-03 | 'onewartwo'B'ewe' |
| 'onewartwo'B'ewe' | rule-13 | 'onewartwoearewe' |
|-------------------+---------+-------------------|
| | | 'onewartwoearewe' |
B -> 'o'
, then it will no longer be ambiguous... $\endgroup$S
. By the application of the ruleS := ...
, we get...
, ..." $\endgroup$